Human Smuggling from The Perspective of Indonesian Positive Criminal Law (A Study of Decision No.257/PID/2021/PT BNA and No.187/Pid.Sus/2023/PN Dum) - Astried Kusumaningrum; K Kuswardani (Universitas Muhammadiyah Surakarta, 2024)
Lack of awareness of the crime of human smuggling and economic concerns are major factors in the occurrence of such illegal acts. While there may be victims in human smuggling, it is more of a risk of the activity rather than something that is premeditated. Deception, coercion and violence are important elements in human trafficking. The existence of this research aims to find out the extent of Indonesia's policy to tackle the problem of human smuggling in Indonesia and increase the effectiveness of law enforcement against human smuggling which cannot be done instantly, so there needs to be a continuous process. This research uses normative juridical methods and analyzes data qualitatively. The researcher processes and presents data from various sources to produce conclusions and findings based on research efforts. The results showed that the juridical consideration of the judge was the reason for imposing a fine in accordance with the provisions of the law to the defendant. In addition, there are non-juridical considerations of the judge that aggravate the punishment of the defendant, such as the defendant's actions that are contrary to the government's efforts in enforcing immigration laws and the defendant's previous conviction history.